Metode Pembelajaran Kinestetik-Auditori Visual dalam Pembelajaran Bahasa Arab bagi Non Penutur Asli - Risky, Abu; Wantini, Wantini (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2024)
Learning methods are one of the factors that determine the success of learning delivered to students. Students have different characteristics in terms of learning styles and abilities. So the task of a teacher or lecturer is to understand this, so that the lessons delivered can be understood by students. his research aims to analyze the Kinesthetic-Audiovisual learning method as an application for Arabic language learning for non-Arabs. This research uses a descriptive qualitative type. Data collection techniques through interviews, observation and collecting data through documents. From the results of this research it was found that Kinesthetic-Audio-visual learning method in Ma'had Abdurrahman Bin Auf went well and systematically starting from planting concepts, understanding concepts, training participants' skills, evaluation, Apperception to Mandatory Manzili or daily tasks, run well so that students or students who are non-Arabic can follow the KBM well and enthusiasti. This method can be applied in community empowerment programs through Arabic language education, such as in Islamic boarding schools, formal education institutions and mosques, so that Arabic language skills can be useful in religious and social activities.